Web-based for UiTM Arau food order / Nur Zahirah Izzati Mohd Zahir and Zulfikri Paidi - Mohd Zahir, Nur Zahirah Izzati; Paidi, Zulfikri (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The UiTM Online Food Ordering web-based system is a computerised system created to make it simpler for UiTM staff and students to purchase food and beverages. This technology was developed in response to the present lack of an automated system, which is depending on paper orders and long queues. The need for social isolation and the ongoing COVID-19 pandemic have highlighted the significance of a computerised system to improve cafeteria management and accessibility. The UiTM Arau Food Order System was developed using the Waterfall method, which includes stages including planning, information gathering, requirements analysis, design, development, implementation, and testing. The user experience is given top priority, and features like email integration for purchase tracking and alerts are included. The system was evaluated for usability and functionality by prospective end-users, and the response time was tested using network performance testing. With 32 respondents, the results showed that the system met its objectives and was successful.